Strategic Management a Dynamic View - Lawrence Emeagwali, Okechukwu (IntechOpen, 2019)
Through select contributions, this edited volume presents a current discourse on strategic management specifically through the lens of industry dynamism. It re-examines the enduring call for dynamic strategies and capabilities at the firm and industry level, drawing case studies from a diverse array of geographic locations. Its findings are presented in two succinct sections: "On Dynamic Strategies" and "On Dynamic Capabilities," which collectively read as a unit.